Follicular lymphoma of the ocular adnexal region: A nation‐based study. (13th August 2014) - Rasmussen, Peter K.; Ralfkiaer, Elisabeth; Prause, Jan U.; Sjö, Lene D.; Specht, Lena; Rossing, Henrik H.; Siersma, Volkert D.; Heegaard, Steffen
Abstract Purpose To characterize the clinicopathological features of follicular lymphoma of the ocular adnexal region. Methods Retrospective nation‐based study of Danish patients with ocular adnexal follicular lymphoma from January 1st 1980 through December 31st 2009. Results Twenty‐four patients with ocular adnexal follicular lymphoma were identified. Fourteen (58%) of the patients were females. The median age was 63 years (range: 42–96 years). Eleven (46%) of the patients had primary ocular adnexal lymphoma, seven (29%) had an ocular adnexal lesion in conjunction with a concurrent systemic lymphoma and six patients (25%) presented with an ocular adnexal relapse. The most frequently affected sites were the lacrimal gland (38%) and the orbit (33%). Thirteen patients (54%) presented with Ann Arbor stage IE lymphoma, four (17%) had stage IIE, two patients (8%) stage IIIE, and five patients (21%) had stage IV lymphoma. Radiotherapy was primarily used in patients with primary lymphoma and those with a stage IE/IIE relapse (82%), while stage IIIE/IV lymphomas most frequently received alkylating chemotherapy (67%). Complete remission was observed in 19 of the patients (79%), but of these 11(58%) had a relapse. The 10‐year overall survival for the entire cohort was 59%. The translocation t(14;18) was detected in 16 patients (16/24, 76%). Recurrence was only observed in patients with the t(14;18) (p = 0.05, log‐rank). Conclusions Ocular adnexal follicular lymphoma is more commonly found in elderly female patients. The lacrimal gland is relatively frequently involved. Radiotherapy is the treatment of choice for localized ocular adnexal follicular lymphoma providing a favourable prognosis for majority of patients.